CONSUMER RIGHTS AND CONTRACT FAIRNESS: COMPARATIVE STUDY - Kubaeva Ismigul Farkhod Kizi (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to compare the regulation of consumer contracts and unfair terms in the European Union (EU) and Uzbekistan, focusing on legal safeguards to protect consumers as the weaker party in contractual relationships. The research evaluates the extent to which these jurisdictions address information asymmetry and power imbalances through their legislative frameworks, with particular emphasis on the EU’s Unfair Contract Terms Directive (UCTD) and Uzbekistan’s broader consumer protection laws. Methods: The research employs a comparative legal analysis, reviewing legislative texts, judicial interpretations, and relevant case studies from both the EU and Uzbekistan. It examines the principles underlying the EU’s harmonized regulatory framework, including the contra proferentem rule and partial nullity, and contrasts these with Uzbekistan’s reliance on general prohibitions and undefined criteria for fairness in consumer contracts. Additionally, the study assesses the practical implications of these legal approaches for consumers and businesses. Results: The findings reveal significant differences in consumer protection mechanisms between the EU and Uzbekistan. The EU’s detailed and harmonized framework offers clear definitions, illustrative examples, and principles to mitigate power imbalances, ensuring consistent application across member states. In contrast, Uzbekistan’s legislation lacks specific criteria for unfair terms, leading to potential inconsistencies in judicial practice and weaker consumer trust in regulatory protections. Novelty: This study contributes to the comparative discourse on consumer protection by highlighting the advanced features of the EU’s legal framework and identifying gaps in Uzbekistan’s approach. It proposes adopting key elements of the UCTD, such as defining unfair terms, incorporating criteria like significant imbalance and breach of good faith, and introducing protective measures for pre-drafted contracts. These insights provide valuable guidance for policymakers seeking to strengthen consumer protection in developing legal systems.